2008
DOI: 10.1063/1.2903512
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the origin of deep levels in CdTe doped with Bi

Abstract: Combining optical ͑low temperature photoluminescence͒, electrical ͑thermoelectric effect spectroscopy͒, and structural ͑synchrotron X-ray powder diffraction͒ methods, the defect structure of CdTe doped with Bi was studied in crystals with dopant concentration in the range of 10 17 -10 19 at./ cm 3 . The semi-insulating state observed in crystals with low Bi concentration is assigned to the formation of a shallow donor level and a deep donor recombination center. Studying the evolution of lattice parameter with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 40 publications
0
10
1
Order By: Relevance
“…The results of this simulation demonstrated that the Te-Te configurational equilibration position is far from a dimer formation in these conditions and instead a simple Bi cd substitution without structural distortion appears. This theoretical result is different from the prediction of Saucedo et al [9], but a tetrahedral to octahedral distortion is in fact what should happen in CdTe:Bi. Du [14] points out that Bi in CdTe located at the Cd position and interacting with oxygen substituting tellurium (Bi cd +0 Te ) adopts a C 3v symmetry that is coherent with a Jahn Teller distortion [15].…”
Section: Introductioncontrasting
confidence: 56%
See 4 more Smart Citations
“…The results of this simulation demonstrated that the Te-Te configurational equilibration position is far from a dimer formation in these conditions and instead a simple Bi cd substitution without structural distortion appears. This theoretical result is different from the prediction of Saucedo et al [9], but a tetrahedral to octahedral distortion is in fact what should happen in CdTe:Bi. Du [14] points out that Bi in CdTe located at the Cd position and interacting with oxygen substituting tellurium (Bi cd +0 Te ) adopts a C 3v symmetry that is coherent with a Jahn Teller distortion [15].…”
Section: Introductioncontrasting
confidence: 56%
“…This result implies a high oxygen co-doping. However, these aforementioned experiments [8,9] are made restricting oxygen concentration range to the 10 14 -10 15 cm~3 level [16]. Therefore this cannot be the explanation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations